2008
DOI: 10.1111/j.1365-2664.2008.01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal shifts in dung beetle community structure within a protected area of tropical wet forest: a 35‐year study and its implications for long‐term conservation

Abstract: Summary1. Throughout much of the tropics, habitat loss is increasing and intensifying on the unprotected land surrounding conservation areas. The influence of these land-use changes on biodiversity is poorly understood. This study used data on dung beetles, a taxonomic group widely acknowledged to be an effective ecological indicator of anthropogenic disturbance, to evaluate temporal changes in diversity inside a natural protected area. 2. Using data from quantitative sampling events over the last 35 years alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 34 publications
3
37
0
11
Order By: Relevance
“…The total number of species for this landscape is 28, including one introduced species (Digitonthophagus gazella). All the evidence indicates that this high degree of complementarity between sites, found also in other tropical forests Escobar et al 2008;quintero & Halffter in press), occurs in the lower part of the Hidalgo transect (on the slope down to the Gulf-Las Huastecas), although this has not been studied specifically.…”
Section: Comparison With Other Transectsmentioning
confidence: 98%
“…The total number of species for this landscape is 28, including one introduced species (Digitonthophagus gazella). All the evidence indicates that this high degree of complementarity between sites, found also in other tropical forests Escobar et al 2008;quintero & Halffter in press), occurs in the lower part of the Hidalgo transect (on the slope down to the Gulf-Las Huastecas), although this has not been studied specifically.…”
Section: Comparison With Other Transectsmentioning
confidence: 98%
“…Since they are relatively short-lived, have large populations, and are sensitive to environmental alterations, dung beetles can respond quickly to forest changes (Nichols et al 2007;Larsen et al 2008;Rös et al 2012). Dung beetle assemblages in fragmented landscapes have been shown to be affected by forest patch size (Klein 1989;Andresen 2003), landscape forest cover (Rös et al 2012), edges (Spector and Ayzama 2003), patch isolation (Arellano et al 2008a;Escobar et al 2008), matrix type (Klein 1989;Quintero and Roslin 2005), and other spatial variables, such as altitude and slope (Silva and Hernández 2014). Most of these studies evaluate the effects of one or a few attributes at one spatial scale (but see Silva and Hernández 2014), thus limiting the control of potential confounding factors (Ewers and Didham 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The present study indicated that the fragmentation of large intact natural forests did not affect the assemblages of dung beetles for about 10 years. However, a 35-year study indicated that environmental changes degraded the beetle fauna around a forest reserve, regardless of forest protection (Escobar et al 2008). It is known that the sensitive, large-bodied, rare forest dung beetles need at least 85 ha forest to survive (Larsen et al 2008), and the core area of BBF is ca.…”
Section: Findings Other Than Plantationmentioning
confidence: 99%